Geographical Considerations for Implementing Autonomous Unmanned Solar-HAPS for Communications Area Coverage - Anicho, Ogbonnaya; Charlesworth, Philip B; Baicher, Gurvinder; Nagar, Atulya (Talenta Publisher, 2019)
The impact and requirements for implementing stratospheric or high altitude vehicles for communications coverage may vary from one geographical location to another. These variations may impose significant constraints on energy and various key parameters of the vehicle’s operation and performance.This paper therefore, examines the potential for autonomous fixed-wing unmanned solar-powered High Altitude Platform Station or Pseudo-Satellite (HAPS) to provide persistent communications coverage. As a solar dependent platform, the potential for harnessing green energy and long platform endurance makes it an attractive communications coverage option. However, the variation of latitude and seasons across the globe presents an implementation constraint and challenges power availability and coverage capability. This paper investigates how the services of a typical solar-powered HAPS are affected by latitude and season. It shows that the degree of insolation directly affects the unmanned aircraft’s altitude, hence, its footprint diameter and power available to the communications payload. The paper highlights effective energy management algorithms as key to successful implementation of solar-powered unmanned HAPS especially at challenging latitudes and seasons